The Acquisition, Organization, and Preservation of Information in Ancient Libraries - Olson, Leanne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Research Roundtable: This paper examines select secondary source literature on ancient library history, focusing on techniques used in ancient libraries for the acquisition, organization and preservation of information. It analyzes ancient principles of librarianship embedded in these methods and their relevance to modern-day libraries. Tables rondes: Cette communication examine certaines sources de littérature secondaire sur l’histoire des bibliothèques anciennes, plus précisément les techniques utilisées dans les bibliothèques anciennes pour acquérir, organiser et préserver l’information. On y analyse les principes anciens de bibliothéconomie qui transparaissent de ces méthodes ainsi que leur pertinence pour les bibliothèques modernes.